The role of multiple intelligences: For career guidance and counselling services for vocational high school teachers - Hadi, Abdul; Suwidagdho, Dhanang; Ningsih, Ruly (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
The purpose of this study was to determine the role of multiple Intelligence on Career Guidance and Counselling Services for Guidance and Counselling Teachers at Vocational High School 1 Klaten. This research uses qualitative research with the type of field research (Field Research). The subjects of this study were all Guidance and Counselling Teachers at Vocational High School 1 Klaten. Data collection techniques in this research are interviews and observations. The data used in this research is descriptive data analysis with the stages: data reduction, data presentation, and conclusion. The results showed that multiple Intelligence plays an essential role in career guidance and counselling services by guidance and counselling teachers at Vocational High School 1 Klaten.